Bioanalytical techniques - Talluri, Sekhar (I.K. International Publishing House, 2012)
Focuses on conventional bioanalytical and biophysical tools, emerging techniques, and instruments and probes the molecular aspects of biological systems. This book provides the readers with the fundamentals and basic techniques such as sensors, separations, mass spectrometry, spectroscopy, arrays, microfluidics, and more